New approaches an example from Zambia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The Kenyan experience in establishing a successful national soil conservation programme led to the creation of the SIDA (Swedish International Development Authority) funded Regional Soil Conservation Unit (RSCU) based in Nairobi. The aim of the...